At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex] \frac{-2+x}{2}=1 [/tex]∧[tex] \frac{3+y}{2} =0[/tex]⇔[tex]x = 4[/tex] ∧[tex]y = -3[/tex]
R: D (4, -3)
R: D (4, -3)
Answer:
The other endpoint
[tex](x_{2} , y_{2}) is (4,-3)[/tex]
Step-by-step explanation:
Given
Point 1 (-2,3)
Midpoint = (1,0)
We're to calculate the other end point.
To solve this, we'll make use of the formula of midpoints of line
Given that two lines of coordinates [tex]P(x_{1} ,y_{1} )[/tex] and [tex]Q(x_{2} ,y_{2} )[/tex]
[tex](m_{1},m_{2}) = (\frac{(x_{1} + x_{2} )}{2} ,\frac{(y_{1} + y_{2} )}{2})\\Where\\m_{1} = \frac{(x_{1} + x_{2} )}{2} \\and\\m_{2} = \frac{(y_{1} + y_{2} )}{2})\\[/tex]
From the question, we have
[tex]m_{1} = 1\\m_{2} = 0\\x_{1} = -2\\y_{1} = 3\\[/tex]
Calculating [tex]x_{2}[/tex]...
From [tex]m_{1} = \frac{(x_{1} + x_{2} )}{2}[/tex]
By Substitution, we have
[tex]1 = \frac{-2+x_{2} }{2} \\2 = -2+x_{2}\\2 + 2 = x_{2}\\ x_{2} = 4[/tex]
Calculating [tex]y_{2}[/tex]...
From [tex]m_{2} = \frac{(y_{1} + y_{2} )}{2}[/tex]
By Substitution, we have
[tex]0 = \frac{3+y_{2} }{2} \\0 = 3+y_{2}\\0 - 3 = y_{2}\\ y_{2} = -3[/tex]
Hence, the other endpoint
[tex](x_{2} , y_{2}) is (4,-3)[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.